Química e arte: uma sequência didática para o ensino/aprendizagem de química para a 2ª série do ensino médio - Chaiben, Leize Aparecida (2021)
The teaching/learning process that involves the discipline of Chemistry in High School has been increasingly discussed in recent years, because over the years it is possible to observe the lack of motivation of the students regarding the discipline. Since generally this discipline has been structured around activities that lead to the memorization of information, formulas and knowledge that limit the teaching/learning of students and end up contributing to this demotivation in learning and studying Chemistry.Usually, the bimonthly/quarterly works of educational institutions are based on the choice of the topic to be worked on, the teacher determines a deadline, whether it will be developed individually or in groups and whether it will be delivered in handwritten form or printed in physical form or also, via e-mail or “PowerPoint” presentation. Aiming to make classes and assignments more attractive to students and at the same time make them interested in the discipline, the objective of this work is to develop a didactic sequence (SD) using musical parodies and theater as a didactic tool for teaching / learning chemical concepts involving Thermochemistry, using music and theater in the search for a dynamic, contextualized and meaningful teaching of Chemistry. The didactic sequence presented in this work was applied in the Second Grade of High School, in a private school in the city of Foz do IguaçuPR. For the development of the work, guiding questions, multimedia, concept maps, videos and finally to fix the contents, the development of parodies and from the theatre. As the proposals for parodies and theater are to facilitate the teaching/learning process, all creations and presentations were carried out before the quarterly tests. For the first moment of each quarter, a questionnaire was applied with each topic worked on in order to identify the students' prior knowledge. It was possible to observe right after the quarterly tests that, making an observation with the previous tests with the Thermochemistry content, the students had a significant increase in the assimilation of the content. During the development of activities, it was understood that different evaluative methodologies (parodies and theater) in teaching/learning Chemistry can and should be used more frequently.